Electronic Payment System: Types, Trends, and its Impacts on Thai Economy - Suwanragsa, Issara; Sinliamthong , Pathathai; Srivalosakul, Pallapa; Tangjitprom, Nopphon; Srinutshasad, Chainarin (Journal of Contemporary Social Sciences and Humanities, 2025)
Electronic Payment helps enhancing economic growth, promoting online trading, decreasing cash holding, and reducing friction in trade transactions, resulting in an increase in private consumption expenditure (PCE) and real gross domestic product (RGDP) in the country. There are various forms of E-payments; however, the examination of each type of E-payments regarding its trends and impacts on the emerging economy is still limited. The present study fills this gap by exploring types, trends, and relationships between E-payments and the impacts on Thai economy. Literature review was employed to explore the characteristics of each type of E-payments. Descriptive statistics was applied to explore the trends of E-payments during 2010-2020. Pearson correlations and regression analysis using Newey-West standard errors were employed to analyze the effects of E-payments growth on PCE growth and RGDP growth in Thailand. The results indicated that E-payments were significantly and positively related to PCE growth and RGDP growth. Payment transactions via Internet/Mobile banking and E-Money increased remarkably, while transactions via ATM cards decreased over time. Transactions via debit cards remained stable, whereas transactions via credit cards showed a slightly increasing trend. Credit cards, Internet/Mobile banking, and E-Money positively and significantly related to PCE growth and RGDP growth, while there were no relationships between ATM cards relating to PCE growth and RGDP growth in Thailand. Overall, a 1% growth in E-payments results in 0.13% growth in PCE and 0.12% growth in RGDP.